2017
DOI: 10.1111/liv.13501
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in complications of chronic hepatitis C

Abstract: Although cirrhosis and mortality among HCV-infected patients in the US have increased over the past decade, all-cause mortality has decreased in recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This observation is consistent with recent studies that have demonstrated higher rates of cirrhosis among black and Hispanic patients and lower HCV treatment rates among racial minorities. (1113) This trend also parallels the racial trends of LT overall, which may represent improved access to LT for minorities, who have been historically disadvantaged. (1415)…”
Section: Discussionmentioning
confidence: 74%
“…This observation is consistent with recent studies that have demonstrated higher rates of cirrhosis among black and Hispanic patients and lower HCV treatment rates among racial minorities. (1113) This trend also parallels the racial trends of LT overall, which may represent improved access to LT for minorities, who have been historically disadvantaged. (1415)…”
Section: Discussionmentioning
confidence: 74%
“…Approximately 2.4 million US individuals are currently infected with the hepatitis C virus (HCV) 1 and 28% of those with chronic HCV have cirrhosis. 2 Annually 1% to 4% of individuals with cirrhosis will develop liver cancer. 3 Antiviral treatments for HCV previously required a combination of agents taken over 24 to 48 weeks, were associated with significant adverse effects, and were effective in 54% to 63% of patients who completed treatment.…”
Section: Introductionmentioning
confidence: 99%
“…First, because infection with HCV is primarily asymptomatic, undiagnosed baby boomers are experiencing the downstream effects of the disease decades later. Recent analyses have revealed an increase in two critical HCV‐related outcomes, cirrhosis and hepatocellular carcinoma . Second, injection drug use, the predominant risk for HCV transmission, has increased in concert with the nation’s opioid epidemic .…”
mentioning
confidence: 99%
“…Recent analyses have revealed an increase in two critical HCV-related outcomes, cirrhosis and hepatocellular carcinoma. (6,7) Second, injection drug use, the predominant risk for HCV transmission, has increased in concert with the nation's opioid epidemic. (8) Moreover, among persons successfully treated and cured, active drug injection poses a major risk of reinfection.…”
mentioning
confidence: 99%